KARAKALPAKISMS AND RUSSIAN-LANGUAGE FICTION TEXT - Dospanova, D.U. (SCIENCE and SOCIETY, 2022)
It is discussed how Karakalpakisms have influenced on Russian-language fiction. As an example presents the works by Karakalpak authors that have been translated or written in Russian.
Keywords: Karakalpakisms; mutual enrichment; mutual influence; borrowing; lexicon